(untitled) (CAHIERS MAGELLANES-NS, 2024)
The rapid proliferation of social media has revolutionized the landscape of marketing, offering unprecedented opportunities for brands to engage with consumers. This review paper examines the influence of social media marketing on fintech brand equity, particularly in the context of emerging economies. By synthesizing existing literature, we explore how social media strategies enhance brand visibility, trust, and customer loyalty for fintech companies operating in these regions. The study highlights key elements of effective social media marketing, including content quality, influencer partnerships, and interactive campaigns, and assesses their impact on brand equity dimensions such as brand awareness, perceived quality, and brand associations. Furthermore, the paper discusses the unique challenges and opportunities fintech firms face in emerging markets, where digital infrastructure and consumer behavior significantly differ from developed economies. The findings reveal that successful social media marketing not only boosts brand equity but also facilitates financial inclusion by reaching underbanked populations. This review identifies gaps in the current literature, particularly the need for empirical studies focusing on specific fintech sub-sectors and regional variations within emerging economies. The analysis underscores the importance of adapting social media strategies to local contexts to maximize their effectiveness. It also suggests that future research should investigate the long-term impact of social media marketing on fintech brand equity and its correlation with business performance metrics. By providing a comprehensive overview of the interplay between social media marketing and fintech brand equity in emerging economies, this paper offers valuable insights for practitioners and researchers aiming to leverage digital platforms to enhance brand value and drive growth in the fintech sector.